The Eroding Effect of Corruption on System Support in Sweden. Issue 4 (21st November 2012) - Linde, Jonas; Erlingsson, Gissur Ó
Abstract : Sweden is consistently found at the top in international indices of corruption. In recent years, however, several instances of corruption have been exposed, and surveys show that large shares of Swedish citizens harbor perceptions that public corruption is widespread. Drawing on recent surveys, two questions are asked. First, to what extent do Swedish citizens believe that corruption constitutes a serious problem? Second, how do citizens' evaluations of the extent of public corruption affect support for the democratic system? Approaching the issue from a comparative Nordic perspective, the data indicate that Swedes are considerably more prone to believe that politicians and public officials are corrupt than their Nordic counterparts. The analysis also suggests that such perceptions constitute an important determinant of support for the democratic system. Thus, even in a least likely case of corruption, such as Sweden, growing concerns about corruption has a potential to affect democratic legitimacy negatively.